Dynamic Low Voltage Ride through Detection and Mitigation in Brushless Doubly Fed Induction Generators - Ahsanullah Memon; Mohd Wazir Mustafa; Muhammad Naveed Aman; Mukhtar Ullah; Tariq Kamal; Abdul Hafeez (Energies, 2021)
Brushless doubly-fed induction generators have higher reliability, making them an attractive choice for not only offshore applications but also for remote locations. These machines are composed of two back-to-back voltage source converters: the grid side converter and the rotor side converter. The rotor side converter is typically used for reactive current control of the power winding using the control winding current. A low voltage ride through (LVRT) fault is detected using a hysterisis comparison of the power winding voltage. This approach leads to two problems, firstly, the use of only voltage to detect faults results in erroneous or slow response, and secondly, sub-optimal control of voltage drop because of static reference values for reactive current compensation. This paper solves these problems by using an analytical model of the voltage drop caused by a short circuit. Moreover, using a fuzzy logic controller, the proposed technique employs the voltage frequency in addition to the power winding voltage magnitude to detect LVRT conditions. The analytical model helps in reducing the power winding voltage drop while the fuzzy logic controller leads to better and faster detection of faults, leading to an overall faster response of the system. Simulations in Matlab/Simulink show that the proposed technique can reduce the voltage drop by up to 0.12 p.u. and result in significantly lower transients in the power winding voltage as compared to existing techniques.